10th International Conference on Nuclear Engineering, Volume 3 2002
DOI: 10.1115/icone10-22520
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Minimum Film Boiling Temperature for Vertical Cylinders at Elevated Pressure

Abstract: The minimum film boiling temperature, Tmin, is of particular interest to nuclear safety. Many thermal-hydraulics codes depend on an accurate estimation of Tmin to determine the appropriate heat transfer regime. Heat transfer coefficients increase considerably when the surface temperature decreases below Tmin. This paper presents the results of an experimental investigation of Tmin for vertical cylinders at elevated pressure. While several previous studies have investigated Tmin under various conditions, relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…The disagreement between the experimental and predicted data could be due to the other effects such as surface conditions and vapor film collapse mode. Peterson and Bajorek (2002) concluded that T min has a strong, positive relationship with pressure at pressures below 1.0 MPa. Therefore, Berenson's correlation predicts T min accurately at lower system pressures compared to Henry's correlation which does not adequately account for a pressure effect on T min .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The disagreement between the experimental and predicted data could be due to the other effects such as surface conditions and vapor film collapse mode. Peterson and Bajorek (2002) concluded that T min has a strong, positive relationship with pressure at pressures below 1.0 MPa. Therefore, Berenson's correlation predicts T min accurately at lower system pressures compared to Henry's correlation which does not adequately account for a pressure effect on T min .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, investigating the T min point is essential in areas such as metal heat treating, nuclear engineering industry, in a hypothetical large break lossof-coolant accident (LOCA), evaporators and compressors in the air conditioning systems, refrigeration systems, chemical processes, and oil systems (Pettersson et al, 2009;Ramesh and Prabhu, 2015). T min has been widely studied in terms of various parameters such as substrate material (Peterson and Bajorek, 2002), surface conditions and oxidation (Sinha, 2003;Lee et al, 2014), system pressure (Henry, 1974;Sakurai et al, 1984), flow condition (Groeneveld and Stewart, 1982;Carbajo, 1985), initial surface temperature (Kang et al, 2018), rod diameter (Sakurai et al, 1987;Jun-young et al, 2018), liquid subcooling (Adler, 1979;Freud et al, 2009), vapor-liquid contact angle (Ebrahim et al, 2018), surface roughness and microstructure (Peterson and Bajorek, 2002;Carey, 2020), and alternative quenching fluids (Shoji et al, 1990;Lee and Kim, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of the pool boiling is evaluated by the enhancement in CHF, HTC, T min , and vapor film thickness. In literature, the effects of the following parameters have been studied: substrate material [ 340 ], surface conditions and oxidation [ 341 , 342 ], system pressure [ 343 , 344 ], initial wall temperature [ 345 ], shape and dimension of the testing specimen [ 346 , 347 ], degrees of liquid subcooling [ 348 , 349 , 350 ], surface wettability and vapor–liquid contact angle [ 351 ], surface roughness and wickability [ 352 ], and type of quenchant such as water, oil, or nanofluids [ 353 , 354 ]. Recently, researchers have been focused on the effects of the later parameter on pool boiling heat transfer performance.…”
Section: Thermal Applicationsmentioning
confidence: 99%
“…The authors used cladding materials made of stainless steel 316, Zirconium 702, and Inconel 600. Data taken from only three embedded thermocouples resulted in the authors producing a correlation for T min based on one given by Peterson and Bajorek in 2002 [8], shown in Equation (3).…”
Section: Surface Effect On T Minmentioning
confidence: 99%